Awareness On Minor Disorders Of Pregnancy Among Pregnant Women Of A Hospital - Maharjan, Mamata (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Minor disorders of pregnancy are the common discomforts experienced during pregnancy. These disorders can be unbearable and stressful which may later affect outcomes of pregnancy. The objective of the study was to find out awareness on minor disorders of pregnancy among pregnant women attending antenatal OPD. Methods: A descriptive cross-sectional study was conducted among 91 pregnant women in Bhaktapur hospital by using non - probability convenience sampling technique. Face to face interview technique was used to collect data by using self-developed structured questionnaire. The study was conducted between 27 April 2022 to 27 May,2022. Data management, analysis and interpretation was done using descriptive and inferential statistics and represented in tabulated form. Results: The findings of this study showed that the majority (70.3%) of the respondents had an inadequate level of awareness of minor disorders of pregnancy. Inadequate awareness was present in causes of hemorrhoid, causes of varicose vein 25.3%, and causes of insomnia 44.0% during pregnancy. There was a significant association between levels of awareness on minor disorders of pregnancy with type of family (p=0.017). Conclusion: Awareness on minor disorders of pregnancy among pregnant women is still inadequate, which suggests the need for effective health education program on minor disorders of pregnancy to prevent form complications arise from these disorders.